Fabrication of iron modified screen printed carbon electrode for sensing of amino acids. (1st April 2020) - Tayyab Raza Naqvi, Sayed; Rasheed, Tahir; Naeem Ashiq, Muhammad; Najam ul Haq, Muhammad; Majeed, Saadat; Fatima, Batool; Nawaz, Rahat; Hussain, Dilshad; Shafi, Sameera
Graphical abstract: Highlights: Development of iron modified screen-printed carbon electrode on glass sheath. Electrochemical sensing of amino acids i.e. valine, serine and phenylalanine. Enhanced electrocatalytic activity by the fabricated electrode. The food quality can be tested with the help of as prepared Electrode. Abstract: Amino acids are integrated and degenerated in the process of metabolism in human beings, animals, microorganisms and plants. Determination and sensing of amino acids is important to investigate biochemical processes because of their significance in biological systems. Here, cost effective iron modified screen-printed carbon electrode on glass sheath for the first time was designed for the electrochemical sensing of amino acids. The electrode can easily be modified, and reused after successive cleaning steps of washing with water and acids. Three amino acid, i.e. valine, serine and phenylalanine were filmed separately over the iron modified screen-printed carbon electrode and analyzed via cyclic voltammetric technique. The electrochemical sensor showed distinct oxidation peak at 0.26 V, 0.12 V and 0.18 V for each amino acid i.e valine, serine and phenylalanine, respectively. There is a linear relationship between maximum current of oxidation and concentration of amino acids (R 2 for valine, serine and phenylalanine 0.9988, 0.9983 and 0.9955, respectively). The experimental parameters scan rate, pH, concentration and time of contact were optimized for the detection of these amino acids. Under the optimized conditions, the interference effect from other species were also studied. Sensing of these amino acids at basic pH range and at lower concentrations. The results here reported the preliminary efforts in fabricating low cost and eco friendly electrode for sensing and detection of amino acids individually. Further optimizations and modification, the iron modified screen-printed carbon electrode can be used for the detection of other amino acids, biogenic amines and biologically important molecules.